The Impact Of Social Responsibility On Firm Value - Lisa Ovelia; Arizza Zulia R.J; Hwihanus Hwihanus (International Journal of Economics, Commerce, and Management, 2024)
In Indonesia, Malaysia, Australia, China, and Hong Kong, corporate social responsibility (CSR) is an essential component of corporate strategy. In many countries, its effect on corporate value is a crucial concern. This study aims to summarize the impact of corporate social responsibility on corporate value. Using five international journals and the meta-analysis approach, CSR has been demonstrated to influence business value.